Describing the effect of worksheet-assisted PBL on the students’ critical thinking, numeracy, and responsibility - Rahmawati, Afifah Sausan; Fatonah, Nur Anisa (Universitas Ahmad Dahlan, 2026)
This study aims to describe the effect of the problem-based learning model on students' critical thinking skills, numeracy, and sense of responsibility. The research employed a quantitative approach using a one-group pretest-posttest design. The research subjects were seventh-grade students at SMP Negeri 4 Banguntapan, selected randomly. The instruments used included a critical thinking test, a numeracy test, and a responsibility questionnaire. Data were analyzed both descriptively and inferentially using the paired t-test and N-Gain calculations. The results showed p-values ≤ 0.05, indicating significant differences between pretest and posttest scores in critical thinking, numeracy, and responsibility following the intervention. Therefore, it can be concluded that the problem-based learning model assisted by student worksheets positively influences students’ critical thinking skills, numeracy, and sense of responsibility. The improvements in these three aspects fell into the moderate to high categories. These findings indicate that the problem-based learning model is effective in fostering active student engagement, enhancing higher-order thinking processes, and developing positive attitudes toward mathematics learning.